Inventory of fish species and associations caught by visiting anglers as local potential to support biology education - Hery Fajeriadi; Antung Fitriani (Journal of Environment and Sustainability Education, 2025)
Fishing activities in river ecosystems occur year-round with seasonal variation, yet information on fish species, species interactions, and environmental conditions remains limited. Understanding these dynamics can enrich contextual biology learning in zoology, animal behavior, ecology, and environmental studies. This research aims to inventory fish species and their associations based on catches made by visiting anglers, highlighting local potential for biology learning. A descriptive exploratory design was used through observation, unstructured interviews, and literature review. Data were collected along the river flow of Karang Indah Mandastana Village, Barito Kuala District, over one month (late April and early July). A total of 162 individuals were recorded from five species: Anabas testudineus (67.9%), Rasbora aurotaenia (13.0%), Channa striata (8.0%), Rasbora argyrotaenia (7.4%), and Belontia hasselti (3.7%). Anabas testudineus was found at all observation points and dominated catches during calm or stagnant conditions, whereas Rasbora species dominated during stronger currents associated with morning tides. Species associations were influenced by tidal patterns and current presence. A positive correlation occurred between aquatic vegetation density and fish abundance (Spearman’s ρ = 0.53, p < 0.05), especially for Eleocharis dulcis (ρ = 0.74) and Hymenachne amplexicaulis (ρ = 0.68). Vegetation patches along riverbanks were associated with higher fish frequency. Findings also suggest that Anabas testudineus moves into nearby rice fields during high tides, indicating adaptive behavior to hydrological variation. These ecological patterns shaped by tides, currents, and vegetation show strong potential as contextual biology learning resources to increase student engagement and strengthen environmental relevance.